(untitled) (Gestionar: revista de empresa y gobierno, 2024)
Economic literature has shown that out-of-pocket healthcare spending is the most unequal and inefficient way to finance medical care. It harms household welfare; as it increases family expenses and decreases consumption of basic goods like food. In situations of health "shock", these further aggravate and impoverish households. This study analyzes the impoverishment due to out-of-pocket healthcare spending in Peruvian households during the period 2015-2020. It followed the methodology of the World Health Organization and used the logit model to estimate the determining factors of such impoverishment. The results show that out-of-pocket health spending impoverished, on average, 2.6% of non-poor households, with greater impoverishment during the COVID-19 pandemic in 2020, at 3.53%. It was found that the factors determining impoverishment due to health spending were per capita household income, schooling, presence of chronic discomfort, disability of a household member, unmet basic needs such as inadequate housing, overcrowding and lack of sanitary facilities, low school attendance, and high economic dependency, health insurance. Finally, it was found that non-poor urban households become impoverished to a greater extent compared to rural households.